Engineering subcellular-patterned biointerfaces to regulate the surface wetting of multicellular spheroids - Wang, Luying (2020)
Studying the wetting behaviors of multicellular spheroids is crucial in the fields of embryo implantation, cancer propagation, and tissue repair. Existing strategies for controlling the wetting of multicellular spheroids mainly focus on surface chemistry and substrate rigidity. Although topography is another important feature in the biological micro-environment, its effect on multicellular spheroid wetting has seldom been explored. In this study, the influence of topography on the surface wetting of multicellular spheroids was investigated using subcellularpatterned opal films with controllable colloidal particle diameters (from 200 to 1,500 nm). The wetting of hepatoma carcinoma cellular (Hep G2) spheroids was impaired on opal films compared with that on flat substrates, and the wetting rate decreased as colloidal particle diameter increased. The decrement reached 48.5% when the colloidal particle diameter was 1,500 nm. The subcellular-patterned topography in opal films drastically reduced the cellular mobility in precursor films, especially the frontier cells in the leading edge. The frontier cells failed to form mature focal adhesions and stress fibers on micro-patterned opal films. This was due to gaps between colloidal particles leaving adhesion vacancies, causing weak cell–substrate adhesion and consequent retarded migration of Hep G2 spheroids. Our study manifests the inhibiting effects of subcellular-patterned topography on the wetting behaviors of multicellular spheroids, providing new insight into tissue wetting-associated treatments and biomaterial design.